A decision support system for symptom-based common diseases and image-based skin diseases detection - Joy, Moinul Alam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.